Micromundo hipertextual & educação matemática - Silva, José Eduardo Ferreira da [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
This work, whose focus of interest is in the field of challenges posed by inserting the computer in the math teaching practice everyday, aims to present the development and implementation of a multirepresentacional electronic writing called 'micromundo hipertextual' to then, describe and analyze the data collected for the provision of this computational resource on the internet and, finally, present the project 'livro de areia' as an alternative proposal to the culture of the computer room, in other words, the trend to accommodate computers in an environment outside the classroom, usually deficient in the number of available machines that only reinforces the educational perspective that takes the computer as an end in itself and, therefore, makes the media its message. In short, it is a multidimensional research based on the thinking of Álvaro Vieira Pinto (1909-1987), which seeks to frame the relatively new fact of computer use during the daily math classroom in the structure of a process of thought and practical activity of work that exceeds its content at each stage of time, explains it and allows it to extract conclusions and reasonable projections

Este trabalho, cujo foco de interesse está no domínio dos desafios suscitados pela inserção do computador no cotidiano da prática letiva de matemática tem por objetivo apresentar o processo de desenvolvimento e implementação de uma escritura eletrônica multirepresentacional  denominada 'micromundo hipertextual'  para, em seguida, descrever e analisar os dados recolhidos com a disponibilização desse recurso computacional na internet e, por fim, apresentar o projeto 'livro de areia' como uma proposta alternativa à cultura da sala de informática, ou seja, a tendência de acomodação dos computadores em um ambiente externo à sala de aula, geralmente deficiente quanto ao número de máquinas disponíveis que apenas reforça a perspectiva educativa que toma o computador como um fim em si mesmo e, por isso, faz do meio a sua mensagem. Em síntese, trata-se de uma pesquisa multidimensional pautada no pensamento de Álvaro Vieira Pinto (1909-1987), que procura enquadrar o fato, relativamente, novo do uso do computador no dia a dia da sala de aula de matemática na estrutura de um processo de pensamento e de atividade prática do trabalho, que supera seu conteúdo em cada fase do tempo, explica-o e procura extrair dele conclusões e projeções razoáveis
Keywords: Pinto, Alvaro Vieira 1909; Matemática - Estudo e ensino; Educação - Processamento de dados; Mathematics - Study and teaching